2009
DOI: 10.1213/ane.0b013e3181aa6e95
|View full text |Cite
|
Sign up to set email alerts
|

Children with Infantile Neuronal Ceroid Lipofuscinosis Have an Increased Risk of Hypothermia and Bradycardia During Anesthesia

Abstract: Background Neuronal ceroid lipofuscinoses (NCLs) are a group of autosomal recessive neurodegenerative diseases characterized by lysosomal accumulation of autofluorescent material in neurons and other cell types. The infantile subtype (INCL) is rare (1 in >100,000 births), the most devastating of childhood subtypes, and is caused by mutations in the gene CLN1 which encodes palmitoyl-protein thioesterase-1. Methods To investigate the incidence of hypothermia and bradycardia during general anesthesia in INCL pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
2
11
0
2
Order By: Relevance
“…We found that these animals have thermoregulation defects akin to what has been previously reported in children with INCL [17]. Specifically, with aging, Ppt1 -KO mice drop basal body temperature and during acute cold exposure, these mice develop hypothermia compared with wild-type controls.…”
Section: Discussionsupporting
confidence: 75%
“…We found that these animals have thermoregulation defects akin to what has been previously reported in children with INCL [17]. Specifically, with aging, Ppt1 -KO mice drop basal body temperature and during acute cold exposure, these mice develop hypothermia compared with wild-type controls.…”
Section: Discussionsupporting
confidence: 75%
“…Because all of the patients were young children, most examinations were performed under sedation with propofol 17 . Some late stage patients did not require sedation for the MRI exams.…”
Section: Methodsmentioning
confidence: 99%
“…General anesthesia was administered by staff anesthesiologists as previously reported 19 . Upon completion of the procedures and emergence from anesthesia, children were observed in the post-anesthesia care unit until ready to be transferred to the pediatric ward.…”
Section: Methodsmentioning
confidence: 99%